DNase I-hypersensitive sites in the galactose gene cluster of Saccharomyces cerevisiae. - Proffitt, J H (1985)
Five DNase I-hypersensitive regions were associated with the Saccharomyces cerevisiae galactose gene cluster during both galactose induction and glucose repression of transcription. Four hypersensitive regions were located in areas flanking the GAL cluster genes, and one site occurred within GAL10. A DNase I-hypersensitive region located between the 5' ends of divergently transcribed GAL10 and GAL1 contained sequences essential for the transcription of both genes.